Visual Media Based on Local Wisdom of Janger Kolok Art in Regional Dance Material for Grade VI Arts and Culture Content in Elementary Schools - Kadek Wulan Yuni Mahartini; Maria Goreti Rini Kristiantari; Made Vina Arie Paramita (Jurnal Edutech Undiksha, 2025)
The learning of regional dances in SBdP (Arts, Culture, and Skills) subjects at elementary schools has not been optimal due to the limited availability of learning media suited to the characteristics of students, particularly deaf students. As a result, students’ understanding of the material remains low. This study aims to develop and test the validity and effectiveness of visual media based on the local wisdom of Janger Kolok Performing Art in regional dance learning. The research employed a research and development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects consisted of a content expert, an instructional design expert, a learning media expert, and 16 sixth-grade elementary students. Data were collected through expert validation questionnaires, student trials, and learning outcome tests (post-test). Data analysis was conducted using quantitative descriptive techniques and t-tests. The validation results showed an average score of 92.86% (content expert), 90.62% (design expert), and 90.91% (media expert), categorized as "very good." The effectiveness test obtained a tcount = 2.497 > ttable = 1.753, indicating a significant improvement in students’ understanding. The conclusion of this study demonstrates that local wisdom-based media are effective in improving learning outcomes and supporting the preservation of regional culture in schools. The implication is that this media can serve as a reference for developing culture-based learning and as an effort to preserve cultural heritage for younger generations.